The correlation between the teardrop angle and anterior lunate facet displacement in plating distal radial fractures. (June 2019) - Teunis, Teun; Meijer, Sjoerd; Jupiter, Jesse; ,; Rikli, Daniel
This study aimed to determine the association of teardrop angle and anteroposterior distance with anterior lunate facet displacement and articular congruity before and after anterior plating of distal radial fractures. We included 36 patients with complete intra-articular distal radial fractures with separate anterior lunate facet fragments. On radiographs we determined the teardrop angle and anteroposterior distance. On digital three-dimensional models we measured proximal-distal, anteroposterior and ulnoradial anterior lunate facet displacement, and we outlined the gap surface area. Preoperatively, teardrop angle was highly associated with the extent of anterior lunate facet displacement. Increased anteroposterior distance was mainly associated with articular incongruity after anterior plate fixation. This information may reduce the need of preoperative computed tomography scans in fractures with a normal tear drop angle. This is particularly useful in low-resource settings.